2003
DOI: 10.1046/j.1471-4159.2003.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of muscarinic cholinergic receptors enhances the volume‐sensitive efflux of myo‐inositol from SH‐SY5Y neuroblastoma cells

Abstract: A mechanism used by cells to regulate their volume under hypo-osmotic conditions is the release of organic osmolytes, one of which is myo-inositol. The possibility that activation of phospholipase-C-linked receptors can regulate this process has been examined for SH-SY5Y neuroblastoma cells. Incubation of cells with hypo-osmolar buffers (160-250 mOsm) led to a biphasic release of inositol which persisted for up to 4 h and could be inhibited by inclusion of anion channel blockersresults which indicate the invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 51 publications
(88 reference statements)
7
47
0
Order By: Relevance
“…It has become increasingly clear that agonists of these receptors, and ATP in particular, may accelerate cell-volume recovery under anisosmotic conditions and potently modulate volume-sensitive channels as well as transporters in cells, even in the absence of cell-volume changes (15,28,30,54). It has also been established that signaling linked to G protein-coupled receptors may impact cell volume, as, for example, in mouse Means Ϯ SE values (in nmol/mg of protein) from experiments performed in triplicate are shown.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly clear that agonists of these receptors, and ATP in particular, may accelerate cell-volume recovery under anisosmotic conditions and potently modulate volume-sensitive channels as well as transporters in cells, even in the absence of cell-volume changes (15,28,30,54). It has also been established that signaling linked to G protein-coupled receptors may impact cell volume, as, for example, in mouse Means Ϯ SE values (in nmol/mg of protein) from experiments performed in triplicate are shown.…”
Section: Discussionmentioning
confidence: 99%
“…Two Ca 2ϩ /calmodulin-dependent enzymes known to be activated by H 2 O 2 , the myosin light chain kinase (MLCK), and CaMKII, have also been found to regulate VRACs (20,27,49,50). We therefore explored whether changes in intracellular Ca 2ϩ and the activation of Ca 2ϩ /calmodulin-dependent enzymes are involved in the H 2 O 2 effect.…”
Section: Hydrogen Peroxide Potentiatesmentioning
confidence: 99%
“…However, a number of laboratories have demonstrated that stimulation of GPCRs, including several metabotropic P2Y receptors for ATP and ADP, produces limited activation of a VRAC-like pathway in non-swollen cells and greatly increases its activity in cells exposed to hypoosmotic medium (Jeremic et al 2001;Mongin and Kimelberg 2002;Mongin and Kimelberg 2003;Loveday et al 2003;Darby et al 2003;Franco et al 2004). Depending on the experimental system and the GPCR involved, PKCs have been found to play major or minor roles in the regulation of VRAC activity by GPCR agonists (Loveday et al 2003;Falktoft and Lambert 2004;Mongin and Kimelberg 2005;Heacock et al 2006;Cheema et al 2007;Ramos-Mandujano et al 2007). In HeLa cells, HTC rat hepatoma cells, and Mz-ChA-1 human cholangiocarcinoma cells, PKC activity was found to be critical for hypotonic (i.e.…”
Section: Conventional Pkc Isoforms Are Major Contributors To Vrac Regmentioning
confidence: 99%
“…Several groups discovered that ATP and agonists of several other G-protein coupled receptors (GPCR) strongly increase VRAC activity in swollen cells. GPCR agonists may also produce limited VRAC activation in non-swollen cells of both neural and non-neural origin (Tilly et al 1994;Mongin and Kimelberg 2002;Loveday et al 2003;Darby et al 2003;Franco et al 2004;Falktoft and Lambert 2004;Heacock et al 2006;Cheema et al 2007). Regulation of VRAC activity by several purinergic (ATP) receptors may be especially important in the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation